Biogeography and systematics of endemic island damselflies: The Nesobasis and Melanesobasis (Odonata: Zygoptera) of Fiji. Issue 17 (18th August 2017) - Beatty, Christopher D.; Sánchez Herrera, Melissa; Skevington, Jeffrey H.; Rashed, Arash; Van Gossum, Hans; Kelso, Scott; Sherratt, Thomas N.
Abstract: The study of island fauna has greatly informed our understanding of the evolution of diversity. We here examine the phylogenetics, biogeography, and diversification of the damselfly genera Nesobasis and Melanesobasis, endemic to the Fiji Islands, to explore mechanisms of speciation in these highly speciose groups. Using mitochondrial (COI, 12S) and nuclear (ITS) replicons, we recoveredGarli ‐part maximum likelihood andMrbayes Bayesian phylogenetic hypotheses for 26 species of Nesobasis and eight species/subspecies of Melanesobasis . Biogeographical patterns were explored usingLagrange and Bayes ‐Lagrange and interpreted throughbeast relaxed clock dating analyses. We found that Nesobasis and Melanesobasis have radiated throughout Fiji, but are not sister groups. For Nesobasis, while the two largest islands of the archipelago—Viti Levu and Vanua Levu—currently host two distinct species assemblages, they do not represent phylogenetic clades; of the three major groupings each contains some Viti Levu and some Vanua Levu species, suggesting independent colonization events across the archipelago. OurBeast analysis suggests a high level of species diversification around 2–6 Ma. Our ancestral area reconstruction (Rasp ‐Lagrange ) suggests that both dispersal and vicariance events contributed to the evolution of diversity. We thus conclude that the evolutionary history of Nesobasis and Melanesobasis is complex; while inter‐island dispersal followed by speciation (i.e., peripatry) has contributed to diversity, speciation within islands appears to have taken place a number of times as well. This speciation has taken place relatively recently and appears to be driven more by reproductive isolation than by ecological differentiation: while species in Nesobasis are morphologically distinct from one another, they are ecologically very similar, and currently are found to exist sympatrically throughout the islands on which they are distributed. We consider the potential for allopatric speciation within islands, as well as the influence of parasitic endosymbionts, to explain the high rates of speciation in these damselflies. Abstract : The damselfly genera Nesobasis and Melanesobasis are endemic to the Fiji Islands; despite this limited distribution, these groups are highly speciose. Here we explore species relationships within these groups, showing that speciation has been relatively recent, and that the evolutionary history of these species are more complex than current distributions indicate. We also ask why such species diversity would arise among a group of species that are ecologically very similar.